Analysis of the Process of Recording Accounting and Reporting of Groundwater Tax Receipts - MONGDONG, Jeremia Jonathan Julio; KALANGI, Lintje; KINDANGEN, Wulan (PT Keberlanjutan Strategis Indonesia, 2023)
Groundwater Tax is a local tax imposed on the withdrawal and/or utilization of groundwater, excluded for the withdrawal and/or utilization of groundwater for basic household needs, irrigation of agriculture and smallholder fisheries, worship, and the withdrawal and/or utilization of groundwater regulated by regional regulations. This research was conducted at the Regional Revenue and Financial Management Agency of Tomohon City. The purpose of this research is to analyze the Accounting and Reporting Process of Groundwater Tax Revenue in Tomohon City based on Government Regulation Number 71 of 2010 concerning Government Accounting Standards and Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management. The research method used is a qualitative descriptive method which aims to describe, record, analyze, and interpret the conditions that occur in the research object. The results showed that the Accounting and Reporting Process of Groundwater Tax Revenue at the Regional Revenue and Financial Management Agency of Tomohon City was in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards and Minister of Home Affairs Regulation Number 77 of 2020 concerning Technical Guidelines for Regional Financial Management.